Spiritual intelligence as a foundation for student character development: an analysis based on the thought of Imam al-Ghazali - Anggraini, Dinda; Bakti, Surya (UIR Press, 2026)
Character education is an important aspect in the world of education because it plays a role in shaping the personality, morals, and ethics of students. However, the reality of modern education today tends to emphasize the achievement of cognitive aspects, so that spiritual values ​​are often neglected. This condition has the potential to cause a character crisis in students, therefore this study aims to examine the concept of spiritual intelligence as a basis for student character development according to Imam Al-Ghazali and its relevance in the context of modern education. This study uses a qualitative approach with a library study method. Data sources are obtained from various literature in the form of scientific journals related to spiritual intelligence, character education and Imam Al-Ghazali's thoughts. Then explained using content analysis techniques to systematically identify and interpret relevant concepts. The study's findings indicate that spiritual intelligence plays a key role in shaping students' character, as it integrates intellectual and emotional intelligence with moral values ​​and divine awareness. According to Imam al-Ghazali, character formation centers on cultivating the heart (qalb) through the process of takziyatun nafs (obedience to God), which fosters noble morals such as shiddiq (honesty), istiqomah (steadfastness), fatanah (trustworthiness), amanah (trustworthiness), and tabligh (discipline). These findings confirm that character education based on spiritual intelligence can shape students' character in a more profound, stable, and sustainable manner. Therefore, integrating spiritual intelligence into education is a relevant approach to addressing the challenges of the moral crisis in education.